Contemporary Updates on Clinical Trials of Antiangiogenic Agents in the Treatment of Glioblastoma Multiforme - Kochar, Arshneel Singh (Asian J Neurosurg, 2018)
Glioblastoma multiforme (GBM) has the highest rate of vascular proliferation among solid tumors. Angiogenesis is the central feature of rapid tumor growth in GBM and therefore remains an appealing therapeutic target in the treatment of these highly malignant tumors. Antiangiogenic therapy is emerging as an important adjuvant treatment. Multiple antiangiogenic agents targeting various sites in vascular endothelial growth factor (VEGF) and integrin pathways have been tested in clinical trials of newly diagnosed and recurrent GBMs. These include bevacizumab, enzastaurin, aflibercept, cediranib, and cilengitide. In this review, we discuss the current status and challenges facing clinical application of antiangiogenic treatment including anti-VEGF therapy and integrin pathway agents’ therapy in glioblastoma. Here, we highlight a strong biologic rationale for this strategy, also focusing on integrin pathways. PubMed-indexed clinical trials published in English on antiangiogenic treatment of glioblastomas in the past 5 years were reviewed. The results of the current clinical trials of these agents are presented.